Can you diagnose coeliac disease without the need for a duodenal biopsy?. (24th May 2012) - Hastings, R; Kolic, I; O'Neill, D; Tamhne, S; Weston, M; McDermott, E; Kirkham, SE; Charlton, CPJ
Abstract : Aims: Proposed ESPGHAN guidelines recommend that coeliac disease can be diagnosed in patients with a positive history of suggestive symptoms, positive serology markers for coeliac disease and a response to a gluten-free diet without the need for a duodenal biopsy. In contrast, current NICE guidelines advise that a biopsy showing histological features compatible with coeliac disease is required for a diagnosis. This study examined whether using NICE guidelines versus using proposed ESPGHAN guidelines is likely to prevent unnecessary upper GI endoscopy and biopsy in a substantial number of children. Methods: A retrospective cohort of 70 children with positive serology for coeliac disease who underwent upper intestinal biopsy were investigated. Results of serology testing and histopathology findings discussed at clinicopathological conference were examined. Results: Of the 70 patients, 43 were positive for autoantibodies to both endomysial (EMA) and tissue transglutaminase (tTG). All of the children strongly positive for both markers had a biopsy suggestive of coeliac disease. Overall, 64 (91%) of children who underwent endoscopy had histopathological findings compatible with coeliac disease. Two patients with (weakly) positive serology to both markers had a negative biopsy for coeliac disease. One of these patients had a background of Down syndrome and the other was later diagnosed with fructose intolerance. Three children with negative biopsies were EMA positive but tTG negative. One patient with a biopsy that was not suggestive of coeliac disease was EMA negative and tTG positive. This child went on to show improvement with a gluten-free diet. Conclusion: This small study examined children with positive serological markers for coeliac disease who under NICE guidelines warranted upper GI endoscopy and biopsy. Over 90% showed histopathological findings that were compatible with coeliac disease and all of those children that were strongly positive for tTg and EMA had a positive biopsy and went on to respond to a gluten-free diet. This data suggests that children with symptoms suggestive of coeliac disease and with strongly positive serology can be commenced on a gluten-free diet without the need for duodenal biopsy.